Agronomic Responses of Sweet Corn - Peanut Intercropping to Liquid Organic Fertilizer Grown in Different Dosages of Vermicompost - Fahrurrozi Fahrurrozi; Zainal Muktamar; Sigit Sudjatmiko (AGRIVITA, Journal of Agricultural Science, 2023)
Applying organic fertilizer and intercropping systems are among the techniques for preserving land sustainability in organic vegetable production systems. In organic vegetable production, the use of liquid organic fertilizer has been suggested in addition to the use of solid organic fertilizer. This study evaluates how growth and yields of sweet corn and peanuts grown utilizing row intercropping respond to different vermicomposting dosages. A factorial experiment is arranged using a split-plot design with three replicates. The main plot is vermicomposting dosages; 5, 10, 15, 20, and 25 Mg/ha, and the sub-plot was the applications of liquid organic fertilizer, not fertilized and fertilized with liquid organic fertilizer. Results show that the application of liquid organic fertilizer elevated plant height and leaf area, length, diameter, and weight of husked ears of sweet corn. Vermicomposting increased plant height, husked ear length, husked ear diameter, and husked ear fresh weight of sweet corn. Twenty Mg/ha is the best dosage for producing sweet corn intercropped with peanuts. However, using vermicompost and liquid organic fertilizers did not increase the growth and yields of peanuts. Evaluation of nutrient uptakes by intercropped crops, sweet corn, and peanut, in organic production systems, should be the subject of further study.